Validation of the DSCOVR Spacecraft Mission Space Weather Solar Wind Products - Paul T. M. Loto'aniu; K. Romich; W. Rowland; S. Codrescu; D. Biesecker; J. Johnson; H. J. Singer; A. Szabo; M. Stevens (Space Weather)
Abstract In this paper, we present a statistical validation of the Deep Space Climate Observatory (DSCOVR) solar wind data in the operational space weather archive. The DSCOVR observations of the interplanetary magnetic field (IMF), solar wind velocity, density, and temperature were hourly averaged and compared to measurements from NASA's Advanced Composition Explorer (ACE) and Wind spacecraft. Hourly averages, in general, show good correlations between the satellites for the IMF, solar wind velocity Geocentric Solar Ecliptic (GSE) vx‐component, and density. During the period covered by this study (spanning from late July 2016, when DSCOVR went operational, to the end of 2020), the DSCOVR products show no clear evidence of permanent degradation. However, for plasma parameters, there were periods of disagreement with ACE and Wind. The correlation coefficients (Pearson's r) calculated over the entire study period were similar or the same between DSCOVR versus Wind and DSCOVR versus ACE. For comparisons between DSCOVR and Wind, the IMF Bx and By GSE r were 0.94 and 0.96, respectively, while r for the IMF GSE Bz‐component was 0.88. For solar wind velocity, r was found to be 0.96 for the GSE vx‐component, compared with 0.30 for vy and 0.33 for vz. For density, r was found to be 0.84. DSCOVR density observations tend to overestimate compared to Wind values when the solar wind densities are low (below ∼5/cc), while the agreement between the two spacecraft on IMF measurements tends to increase with decreasing spatial separation.